Estimating the impacts of climate change on crop yields and N2O emissions for conventional and no-tillage in Southwestern Ontario, Canada. (January 2018) - He, Wentian; Yang, J.Y.; Drury, C.F.; Smith, W.N.; Grant, B.B.; He, Ping; Qian, B.; Zhou, Wei; Hoogenboom, G.
Abstract: Accurately predicting the impacts of higher temperatures, different precipitation rates and elevated CO2 concentrations on crop yields and GHG emissions is required in order to develop adaptation strategies. The objectives of this study were to calibrate and evaluate a regionalized denitrification-decomposition (DNDC) model using measured crop yield, soil temperature, moisture and N2 O emissions, and to explore the impacts of climate change scenarios (Representative Concentration Pathways (RCP) 4.5 and RCP 8.5) on crop yields and N2 O emissions in Southwestern Ontario, Canada. This simulation study was based on a winter wheat-maize-soybean rotation under conventional tillage (CT) and no tillage (NT) practices at Woodslee, Ontario, Canada. The model was calibrated using various statistics including the d index (0.85–0.99), NSE (Nash-Sutcliffe efficiency, NSE > 0) and nRMSE (normalized root mean square error, nRMSE < 10%) all of which provided "good" to "excellent" agreement between simulated and measured crop yields for both CT and NT practices. The calibrated DNDC model had a "good" performance in assessing soil temperature. However, there were no differences in simulated soil temperatures between CT and NT treatments and this was attributed to deficiencies in the temperature algorithm which does not consider the insulation effect of surface crop residues in the DNDC model. The DNDC model provided a reasonable prediction of soil water content in the 0–0.1 m depth, but it overestimated soil water content during dry conditions mainly because the model was unable to characterize preferential flow through clay cracks. Under future climate scenarios, soybean and maize yields were significantly increased compared to the baseline scenarios due to the benefits from higher optimum temperature for maize and increased CO2 for soybean. The mean annual N2 O emissions for winter wheat significantly increased by about 38.1% for CT and 17.3% for NT under future RCP scenarios when using the current crop cultivars. However, when a new cultivar with higher TDD (thermal degree days) was used, the mean winter wheat yield increased by 39.5% under future climate scenarios compared to current cultivars and there were significant reductions in N2 O emissions. The higher crop heat units cultivars and longer growing season length would contribute to increased biomass accumulation and crop N uptake. Hence there would be co-benefits with the development of high TDD cultivars in the future as they would not only increase crop yields but also reduce N2 O emissions. Highlights: Modelling crop yield, soil temperature, moisture and N2 O emission using DNDC model The DNDC simulated data showed an overall good agreement with measured datasets. Annual N2 O emissions for winter wheat notably increased under future RCP scenarios. Higher TDD cultivars in the future could increase crop yield and reduce N2 O emissions.